(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2018)
Sikkim is a part of the Eastern Himalayas, which is one of the 34 hotspots for biodiversity in the world. With a total of 689 species, which makes up 50% of the species found in the Sikkim subcontinent, Sikkim has a very high diversity of butterflies given its limited geographic area. Sikkim’s vegetation is primarily influenced by the climate, topography, and elevation. It varies significantly every 900 metres and can be divided into six main types. These vegetation types and altitudinal zones along the Teesta valley in Sikkim were the subject of our study on butterfly diversity. For butterfly sampling, we used a fixed width circular plot method, collecting data from 2,617 points along 23 transects at various elevations. During the course of this study, 6,075 butterflies from 251 species and five families were spotted. Richness, abundance, and diversity of butterfly species peaked in low elevation tropical semi-deciduous forests (300-900 m) and decreased as elevation rose to higher altitudes. Additionally, the proportions of exclusive species decreased monotonically with elevation. Of the five families, Nymphalidae had the most species and abundance in the butterfly community. According to cluster analysis, various types of forests are home to different butterfly community assemblages. A single vegetation type was home to 36% of the species, indicating their restricted distribution. Since butterflies only displayed a limited tolerance for changes in elevation and vegetation, it is crucial to preserve their habitats at the landscape scale for the survival of the butterfly fauna in Sikkim.